Structural variations in root and stem wood of Styrax (Styracaceae) from Brazilian forest and cerrado - Machado, Silvia Rodrigues; Rodella, Roberto Antonio; Angyalossy, Veronica; Marcati, Carmen Regina [UNESP] (Int Assoc Wood Anatomists, 2007)
The genus Styrax L. (Styracaceae) has a wide distribution in Brazil, occurring in diverse ecosystems. To get a better insight into the ecological adaptations of wood structure, we studied two species, S. camporum and S.ferrugineus from the cerrado, and three species, S. latifolium, S. martii and S. leprosus from the Atlantic forest. For each species, the wood of root and stem was analyzed separately and observations included qualitative as well as quantitative wood characteristics. The results show that there were significant anatomical differences between the forest and cerrado species as well as between the root and stem wood within single species. Quantitatively, the most informative features in the root wood that separated the forest from the cerrado, species were diameter, length and number of vessels, length of fibres, and width and frequency of rays. In the stem wood, length and frequency of vessels, length of fibres, and width and frequency of rays were the most informative features. In contrast to the forest species, which had larger vessel diameters in their stem wood, the cerrado species had larger vessel diameters in their root wood. The calculated vulnerability index indicates that all Sryrax species have adaptations to mesic conditions. The cerrado species had the smallest index values, which could be related to the seasonally dry condition of this environment.
Keywords: Styrax; Styracaceae; wood anatomy; root; secondary xylem; stem